EUROPE, A SECOND-HAND POWER IN THE AI WORLD - Vacarelu, Marius (The Policy of National Security, 2023)
In this decade we are witnesses and even actors of the establishment of a new technology, which has the power to change psychological realities, but especially in the sphere of politics and economics.The emergence of Artificial Intelligence – or more precisely the huge leap that this technology has made in recent years – has brought a series of relevant questions, both from a strictly scientific point of view and from a practical perspective. Unlike the previous decade, when perhaps part of the debate seemed too advanced, now we are in full competitive reality. It should not be forgotten that the present, if it is competitive, allows human intelligence to assert itself in conferences, articles and volumes. Since Artificial Intelligence brings with it so many changes in such a short interval and in (too) many fields, it is logical that the number of studies on the subject of its implementation should also grow constantly.Europe's situation in this huge process of change needs to be debated. The specific conditions of the continent raise several issues, and among these, the most important seems to be its position in the global ranking of the implementation of Artificial Intelligence. It is precisely this aspect that I am trying to examine in this text, with the firm promise that in the future I will also research the changes that appear in this huge global competition.
Keywords: Europe; Artificial Intelligence; hierarchies; competition; legislation; resources